Integrating social accountability into the medical curriculum: The Need, Implementation, and Impact measurement - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava; Harshal Gajanan Mendhe; Abhishek Joshi (Wolters Kluwer Medknow Publications, 2024)
Social accountability in medical education deals with the responsibility of medical colleges and health-care facilities to effectively respond to the health-related needs of the communities they cater to. The incorporation of social accountability into the medical curriculum has been linked with multiple benefits for different stakeholders. Considering the utility of social accountability, there is an immense need to integrate the same into the medical curriculum and implement it for the benefit of medical students. The success of social accountability will essentially depend on the kind of partnership of medical colleges with the local community. Upon implementation of social accountability into the medical curriculum, the next step is to ascertain the impact of such initiatives. In conclusion, the adoption of social accountability into medical education can significantly aid in the process of producing compassionate and culturally competent medical graduates. The need of the hour is to adopt a concerted approach to integrate social accountability in the medical curriculum and regularly measure its impact for periodic betterment and reduction in health disparity.